CHALLENGES TO VALUATION OF BIODIVERSITY AND THE WAY FORWARD A CASE STUDY OF ADAMAWA STATE, NIGERIA (AUN INTERNATIONAL CONFERENCE, 2025)
The study was conducted to investigate the Challenges to valuation of Biodiversity in Adamawa State and the way forward. Data collection involved the use of multi-stage technique and random sampling method. It was conducted in the three ecological zones of the state (southern guinea, northern guinea and Sudan Savanah zones). Being a purposive study 210 respondents were selected from the 7 randomly selected Local government area in the state. Structured questionnaires were used to obtain primary data while journal, proceedings, text, brochure and manuals were used to elicit information for secondary data. The Data generated were analyzed using descriptive statistics such as, tables, mean, percentages and charts.  The result on challenges to valuation of biodiversity were as follows indicated by the respondents. complexity of the ecosystem top the list with 21.9 % of the respondents followed by government attitude towards conservation with 18.3 % then anthropological activities 16.6 %, data limitation 12.3 %, missing market 10.1 %, early stage of valuation 7.2 %, budget constraint 5.0 %, population growth 4.1 %, poverty 3.1 % and the least is human-wildlife conflict at 1.4 %. The anthropological activities detrimental to the conservation of biodiversity in the state according to respondents were as follows: hunting (26.4 %), farming (18.3 %), logging (14.0 %), grazing (9.8 %), wildfire (8.0 %), settlement (5.2 %), poverty (4.7 %), population increase (4.2 %), insecurity (3.2 %), infrastructure (2.7 %), fishing (2.4 %) and invasive species (1.2 %). The study recommended that, local communities should be trained to acquire skills in areas such as craft making, motor mechanic, carpentry, mason, modern agricultural practices etc. as a sustainable means of livelihood. Adequate policy and institutional frame work should be put in place for the purpose of management and conservation of biodiversity at the grass root Implement community conservation education programs to strengthen outreach and education campaigns targeting all age groups and literacy levels to promote conservation ethics and ecological knowledge. There should be international cooperation in enhancing domestic capacities because most expertise in valuation are located in developed countries. Further studies for the development of appropriate models for valuation of biodiversity in the state and Nigeria at large should be carried out without delay.